Essays on the economics of crime and occupational licensing - Dacass, Tennecia I. L. (Kansas State University, 2019)
This dissertation consists of three essays on issues associated with labor market regulations and the criminal justice system. The first chapter seeks to examine occupational licensing regulations and the native-immigrant wage gap, while the second and third essays examine the effects of an increase in the incidence of adult incarceration on children's short and long term outcomes in the United States. The first essay, co-authored with Dr. Hugh Cassidy, examines the incidence and impact of occupational licensing on immigrants using two sources of data: the Current Population Survey and the Survey of Income and Program Participation. We find that immigrants are much less likely to have a license than similar natives, and that this gap is largest for non-naturalized immigrants, men, and for workers with the highest level of educational attainment. While, a lack of English proficiency reduces the probability of an immigrant having a license, the licensing rate increases with years since migration, and shows large variations by immigrant region of origin. The wage premiums to having a license are much larger for women than men, but seem to be the same for natives and immigrants after controlling for English language ability. In the second essay co-authored with Dr. Amanda Gaulke, we utilize quasi-experimental methods to provide causal estimates of the intergenerational impact of mass imprisonment. Which parents are sent to prison is not random, and many of the same factors that predict adult imprisonment also predict children's outcome. To minimize bias, we use variation in the timing and implementation of `Three Strikes and You're Out' laws to identify the effect of exposure to adult imprisonment on children's long term outcomes. Using the American Community Survey and difference-in-differences approach to estimate the long-run effects, we show that Three Strikes laws impact male children but not female children. Specifically, Black males are less likely to be employed, but among Black males who enroll in college there is no significant decrease in employment and there is an increase in annual earnings. We show sentence length matters which complements the literature on whether parents are incarcerated matters. In the third essay, I assess whether the association between paternal incarceration and children's outcomes varies with age at exposure and gender by comparing children who were 0-18 years when their biological father or father figure entered jail or prison. I use data from the National Longitudinal Study of Adolescent to Adult Health to estimate the association. The results confirm existing research by providing additional evidence that children in the United States are adversely affected by paternal incarceration, but they also show that the adverse outcomes identified are mainly associated with children exposed during early and late childhood. In particular, I find that children exposed during early childhood, primarily before age six, perform poorly in high school relative to those never exposed. Those separated from their father at an early age due to incarceration (mainly boys) earn less income when compared with boys never exposed. Children exposed during late childhood are also negatively affected by paternal incarceration. Notably, females exposed during late childhood are less likely to complete college, and receive lower income relative to females never exposed.
Keywords: Occupational licensing; Immigration; Intergenerational impacts; Sentencing laws; Imprisonment; Human capital accumulation; Occupational licensing